Key infection stages defending heat stress in high-temperature-resistant Blumeria graminis f. sp. tritici isolates - Zhang, Meihui; Wang, Aolin; Zhang, Cheng; Xu, Fei; Liu, Wei; Fan, Jieru; Ma, Zhanhong; Zhou, Yilin (Frontiers in Microbiology, 2022)
With the increasing of temperature in the winter wheat-growing region in China, the high-temperature-resistant Blumeria graminis f. sp. tritici (Bgt) isolates developed in the fields. To clarify the key infection stages of high-temperature-resistant Bgt isolates defending high temperature and the roles of heat shock protein (HSP) genes in response to heat stress, 3 high-temperature- resistant and 3 sensitive Bgt isolates were selected from 55 isolates after determination of temperature sensitivity to investigate the infection stages and the expression levels of HSP genes, including Bgthsp60, Bgthsp70, Bgthsp90 and Bgthsp104, at 18°C and 25°C. The results showed that formation frequency of abnormal appressoria and inhibition rate of haustoria formation of high-temperature-resistant isolates at 25°C were lower than those of high-temperature-sensitive isolates, while major axis of microcolonies of high-temperature-resistant isolates were higher than those of high-temperature-sensitive isolates at 25℃. The results indicated that haustoria formation and hyphae expansion were the key infection stages of defense against heat stress in high-temperature-resistant isolates. Further analyses of HSP genes found the expression levels of Bgthsp60 and Bgthsp70c were up-regulated at 24 and 72 hours post-inoculation in high-temperature-resistant isolates, while no significant difference was observed for Bgthsp90 and Bgthsp104 genes. Taken together, the basis of high-temperature-resistant Bgt isolates is associated with induced-expression of Bgthsp60 and Bgthsp70c response to heat stress in haustoria formation and hyphae expansion stages.